Analysis of the Renvoi Procedure in Special Cases of Insolvency on Review (Case Study of the Decision of Mahkamah Agung Number 44 PK/Pdt.Sus-Bankruptcy/2021) - Dewi Nawang Wulan; Andi Antonio; Ahmad Munir (Socio Legal and Islamic Law, 2024)
This article discusses the mechanism of renvoi procedures in civil cases specifically for bankruptcy in Indonesia, with a focus on the case study of Supreme Court Decision Number 44 PK/Pdt.Sus-Pailit/2021. The renvoi procedure allows creditors or debtors to dispute the amount of debt that has been acknowledged by the curator in the debt/receivables verification meeting. Through analysis of this decision, this article examines how disputes regarding the amount of debt can proceed to the judicial review stage and highlights the important role of the Supreme Court in providing legal certainty. The results of the analysis show that the renvoi procedure is an important instrument to ensure fairness and accuracy in the bankruptcy resolution process. Even though the amount of the debt has been acknowledged in the verification meeting, new evidence or recalculation can change the amount, and the dispute can be taken to court until a decision with permanent legal force is reached. This case highlights the complexity and importance of procedural review as well as the central role of the Supreme Court in ensuring that the bankruptcy resolution process is fair and in accordance with applicable legal provisions. Keywords: Renvoi Procedure, Bankruptcy, Judicial Review